Towards radiocarbon dating of single foraminifera with a gas ion source - Wacker, Lukas; Lippold, Jörg; Molnár, M.; Schulz, H. (Nuclear instruments & methods in physics research. Section B, Beam interactions with materials and atoms, 2013)
Carbonate shells from foraminifera are often analysed for radiocarbon to determine the age of deep-sea sediments or to assess radiocarbon reservoir ages. However, a single foraminiferal test typically contains only a few micrograms of carbon, while most laboratories require more than 100μg for radiocarbon dating with an accelerator mass spectrometry (AMS) system. The collection of the required amount of foraminifera for a single analyses is therefore time consuming and not always possible. Here, we present a convenient method to measure the radiocarbon content of foraminifera using an AMS system fitted with a gas ion source. CO2 is liberated from 150 to 1150μg of carbonate in septum sealed vials by acid decomposition of the carbonate. The CO2 is collected on a zeolite trap and subsequently transferred to a syringe from where it is delivered to the ion source. A sample of 400μg (50μgC) typically gives a 12C− ion source current of 10-15μA over 20min, yielding a measurement precision of less than 7 per mil for a modern sample. Using this method, we were able to date a single 560μg Cibicides pseudoungerianus test at 14,030±160 radiocarbon years. Only a minor modification to our existing gas handling system was required and the system is fully automatable to further reduce the effort involved for sample preparation.
Available online 20 September 2012
Gesehen am 28.07.2021